Influenza Vaccination Coverage in Children With Neurologic Disorders and Their Siblings, July 2006 to June 2014. Issue 8 (August 2018) - Havers, Fiona P.; Fry, Alicia M.; Peacock, Georgina; Chen, Jufu; Reed, Carrie
Abstract : Children with neurologic disorders are at high risk for influenza-associated complications. We identified 184, 460 children 1–17 years of age with neurologic disorders and 204, 966 siblings in a commercial insurance claims database from July 2006 to June 2014. Among children with neurologic disorders, coverage increased from 22.4% in 2006–2007 to 42.3% in 2013–2014, but remained suboptimal. A lower proportion of siblings were vaccinated. Abstract : Supplemental Digital Content is available in the text.